Book review: Mazov, S. V., & Davidson, A. B. (Eds.). (2021). Russia and Africa. Documents and Materials. 1961 - early 1970s. Moscow: Politicheskaya entsiklopediya publ., 1006 p. (In Russian) - Nigusie Wolde Michael Kassaye (Vestnik RUDN. International Relations, 2022)
-